2010
DOI: 10.1259/dmfr/16076453
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the reproducibility in the interpretation of magnetic resonance images of the temporomandibular joint

Abstract: Objectives: The aim was to determine the intra-and interexaminer reproducibility in the interpretation of MRI of the temporomandibular joint among independent observers, with respect to six specific articular characteristics, and to discover which of these had greater and lesser agreement. Methods: 30 magnetic resonance examinations of temporomandibular joints of adults were independently interpreted by 9 experienced and trained observers at 2 different times. Observers were divided into three groups according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 14 publications
3
21
1
Order By: Relevance
“…This is consistent with the findings of Takano et al, 15 Widmalm et al, 16 Butzke et al 17 and Schmitter et al 8 However, better agreement of the disc shape was found by Tasaki et al 10 One way of increasing the agreement between observers is to reduce the number of categories. This was proposed by Takano et al 15 regarding the finding of joint effusion, and in our study, if the finding of joint fluid was dichotomized to ''yes'' or ''no'', the observer agreement would increase to 80%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is consistent with the findings of Takano et al, 15 Widmalm et al, 16 Butzke et al 17 and Schmitter et al 8 However, better agreement of the disc shape was found by Tasaki et al 10 One way of increasing the agreement between observers is to reduce the number of categories. This was proposed by Takano et al 15 regarding the finding of joint effusion, and in our study, if the finding of joint fluid was dichotomized to ''yes'' or ''no'', the observer agreement would increase to 80%.…”
Section: Discussionsupporting
confidence: 89%
“…A recent publication concluded that examiners do not demonstrate reproducibility in the interpretation of MRI of the TMJ. 17 It seems that the diagnosis ''anterior disc displacement without reduction'' reached the highest kappa values and agreements between observers in different publications. 8,13,[15][16][17] In 80% of the cases the five observers agreed on the diagnosis of the disc in the sagittal plane, a finding that is similar to our results.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Even though MRI is considered appropriate to examine the TMJ, research has reported discrepancies between MRI-based and clinical diagnoses 1,[16][17][18][19][20][21][22] . Additionally, studies that evaluated the reproducibility of this method indicate the occurrence of conflicting values [23][24][25][26][27][28][29] . This may be due to two main factors: image quality and observer skills.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, some authors have reported that training sessions and the definition of clear diagnosis criteria increase MRI reproducibility 24,26,34,35 . Furthermore, lower reproducibility values were detected in studies that assessed the performance of observers from different clinical centers who had not been trained 23,25 . For Nebbe et al 25 (2000), agreement ranged from slight to substantial for the diagnosis of anterior disc displacement with reduction (DDR) and normal disc position (κ ranging between 0.15 and 0.67), while the agreement for DDWR was excellent (κ = 0.91).…”
Section: Introductionmentioning
confidence: 99%